Association analysis between nutritional factors within the genome and the risk of osteoarthritis - Kang, Liangming; Wu, Guihua; Lin, Pengfei; Dai, Wenjuan; Huang, Miao (Frontiers in Nutrition, 2025)
Osteoarthritis (OA) is a multifactorial disease influenced by both genetic and environmental factors. Recent studies suggest that genetic variants involved in nutrient metabolism may interact with dietary factors to modulate OA risk. Understanding these gene-nutrient interactions could inform personalized prevention strategies for OA. We conducted a cross-sectional study involving 500 participants to explore associations between specific genetic variants and OA susceptibility, considering dietary intake. Genotyping focused on polymorphisms in the FADS1 gene (rs174537) related to omega-3 fatty acid metabolism, the VDR gene (rs2228570) involved in vitamin D metabolism, and the IL-6 gene (rs1800795), a marker of inflammation. Dietary intake of omega-3 fatty acids, vitamin D, and antioxidants was assessed using validated food frequency questionnaires. Gene-nutrient interactions were evaluated using multivariable logistic regression models, adjusting for potential confounders. Individuals carrying the G allele of FADS1 who reported low omega-3 fatty acid intake exhibited a significantly increased risk of OA [Odds Ratio (OR) = 1.45; 95% Confidence Interval (CI): 1.10–1.90; p = 0.01]. Similarly, participants with the TT genotype of VDR and insufficient vitamin D intake had a higher OA risk (OR = 1.55; 95% CI: 1.15–2.10; p = 0.005). Furthermore, carriers of the IL-6 GG genotype with low antioxidant consumption showed elevated inflammatory markers and an increased OA risk (OR = 1.60; 95% CI: 1.20–2.15; p = 0.002). Our findings indicate that specific genetic variants in FADS1, VDR, and IL-6 genes interact with dietary factors to influence OA susceptibility. These gene-nutrient interactions underscore the importance of personalized dietary interventions in mitigating OA risk. Future longitudinal studies are warranted to confirm these associations and develop tailored prevention strategies.